Proposed new design scheme of HR marketing centre for HR Marketing Sdn.Bhd at Lot 1677, 1678 Jalan Sultan Yusuf, Ipoh, Perak Darul Ridzuan / Mohd Khairul Shazreen Ahmad Tarmizi - Ahmad Tarmizi, Mohd Khairul Shazreen (Faculty of Architecture, Planning and Surveying, 2011)
Final year project reporting is very important element in diploma level. This is the key role of the individual understanding about the whole aspect in the process of interior design that have been learnt from the basic to the higher level that covered of the presentation of the design and ready to face the real world in this industry. The aim of this project is to create how design scheme and image as well as corporate image for HR centre supported with one stop centre also as into centre and info services space requirement for HR One Stop Centre. The objectives is to attract people to come to the center which can ease people to collect information about the product and also buy the product at the same time. It will be the multifunctional centre that not just a centre but it can a place to enjoy, relax and do business. To complete the requirement of this project, interview, research and observation is being doing to make sure the data are required and will be analyzed in the design process. So the detail about the site including inventory and analysis is very important. Thus, the requirements are depend on the location that has to be strategic, size, image, circulation and the character of the cafe. So the customer will feels more relax, friendly atmosphere, cleanliness, comfort, and convenience.